Museum and Church: Interaction Problems (On the Example of a Situation of Primorsky Krai of the Russian Federation) - Elena Alexandrovna Popravko (Управленческое консультирование, 2018)
The problem of transfer of property to religious organizations arise since the late 1980s against the background of changes in state-confessional relations. These changes affect the interests of other social institutions, including museums. The purpose of this research - to objectively assess existing and possible in future consequences of the transfer of property to religious organizations on the example of cultural heritage of the Primorsky Kray. To achieve this purpose there are analyzed the cases of transfer of «religious» property from 1944 to the present time. The main attention was paid to the two precedents: the transfer in 1990 of the Temple of the Saviour in the Dalnerechensk to Russian Orthodox Church (History Museum of Dalnerechensk from 1970 to 1990); and the transfer in 1997 the Church of St. Paul to Evangelical Lutheran Church in Vladivostok (Museum of the Pacific Navy from 1951 to 1996). The first precedent can be considered as a negative for the development of museums; and the second precedent, on the contrary, allows to see opportunities and analyze the factors to resolve the situation without prejudice for the development of all social institutions: the Museum and the Church.